Effect of the pH on Structural and Optical Properties of Al Doped ZnO Nano Powder Synthesized by Simple Hydrothermal Method - Raj Mohan1, R.; Rajendran2, K.; Sambath1, K.; Saravanakumar1, O.M. (Asian Journal of Chemistry, 2013)
In this present work, ZnO and Al doped ZnO (AZO) nano powders have been synthesized by simple hydrothermal method. Zinc nitrate, hexamethylenetetramine and aluminium nitrate were used as precursors for preparing ZnO and AZO with different pH and molar ratios. The structural and optical characterization of Al doped ZnO and ZnO sample powders have been investigated by X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy, photoluminescence and absorption studies. The SEM and XRD results show that the hydrothermal synthesis can be used to obtain different morphologies of nano particles due to variation in pH value. The photoluminescence measurement of AZO shows that wide range of green emission around 520-550 nm with high intensity. The absorbance study reveals that the AZO samples are good enough to ultra violet rays around 200-220 nm. These properties ensure that AZO can be a suitable material for optoelectronic applications.